Integrating Dynamic Capabilities and Business Model Innovation for Strategic Renewal in The Digital Age - Arslan, Ali; Arslan, Muhammad; Rabail, Nisha (ACADEMIA International Journal for Social Sciences, 2025)
The paper examines how sensing, seizing, and reconfiguring capabilities trigger business model innovation (BMI), to what extent BMI intermediates the relationship between dynamic capabilities and strategic renewal, and in what circumstances the relationship between environmental dynamism and the power of digital technology moderate these relations. A series of six to eight digitally transforming firms were studied in an interpretivist multiple-case design and twenty executive informants, episode timelines were formed by interviewing, internal artifacts, and opportunistic observations and analysed by Gioia-informed coding and cross-case replication. The research is valuable to the unpacking of the capability-BMI-renewal nexus, actionable levers in the governance of experimentation, architectural modularity and incentive alignment. The evidence shows that orchestrated capabilities widen the scope, velocity and novelty of BMI; BMI is the principal channel to renewal whereas direct impacts of capability are mostly temporal and efficiency constrained, and high dynamism and powerful digital intensity magnify the indirect route by accelerating the decision handoff process and facilitated reconfigurability at scale. The conclusion reiterates strategic renewal on the condition of transformation of dynamic capabilities into redesigned value logic with the help of BMI, which depends on the context and governance.